Pengembangan Media Pembelajaran Wayang Profesi Untuk Mengenalkan Jenis Pekerjaan Pada Siswa SD - Dede Trie Kurniawan; Auliya Aenul Hayati; Sri Maryanti (Al-Aulad: Journal of Islamic Primary Education, 2019)
This study aims to develop the lecture method of prospective elementary school teachers in utilizing puppet media as an implementation of local wisdom and storytelling skills in explaining the job profession to elementary school students. The use of puppets as learning media in the form of fairy tales contains subject matter that is rich in the applicative value of character education and moral values for students. Puppet shows can make learning more effective and efficient because of the elements of education such as students, educators, educational interactions, educational goals, subject matter, tools and methods and the educational environment to be fulfilled. One example of a theme in the 2013 curriculum that can use the puppet profession as an educational medium of moral value is the theme "Various Works" intended for fourth grade students of Elementary School. The method used to achieve the goal is through Development Research with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation) which is directed at developing puppet media and fairy-tale texts that explain the occupational profession to elementary school students. This study seeks to develop lecture methods that can provide storytelling skills and make puppet media for prospective elementary school teacher students in one of the private colleges of the city of Cirebon in explaining my theme material and my dreams for elementary school students. Keywords: Traditional Puppet, Elementary School Learning Media, Thematic Basic Education